2008
DOI: 10.1111/j.1574-695x.2008.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling ofFrancisella tularensisinfected peripheral blood mononuclear cells: a predictive tool for tularemia

Abstract: In this study, we analyzed temporal gene expression patterns in human peripheral blood mononuclear cells (PBMCs) infected with the Francisella tularensis live vaccine strain from 1 to 24 h utilizing a whole human Affymetrix gene chip. We found that a considerable number of induced genes had similar expression patterns and functions as reported previously for gene expression profiling in patients with ulceroglandular tularemia. Among the six uniquely regulated genes reported for tularemia patients as being part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…and persisting up to 1 week. These responses share many similarities with findings from studies of mice and humans (7,9,12,15,19,22,24,40,49,65), suggesting that zebrafish are a useful and relevant comparative model system to study hostpathogen interactions during Francisella infection.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…and persisting up to 1 week. These responses share many similarities with findings from studies of mice and humans (7,9,12,15,19,22,24,40,49,65), suggesting that zebrafish are a useful and relevant comparative model system to study hostpathogen interactions during Francisella infection.…”
mentioning
confidence: 58%
“…However, in another study using a much lower multiplicity of infection to infect peripheral blood mononuclear cells, there was no downregulation of TNF-␣. Rather, a slight delay in induction was observed (49). The ability to suppress or delay the activation of very specific immune responses may be an important virulence mechanism utilized by Francisella (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the role of IL-17 in tularemia due to findings by others that IL-17 and IL-23 (which can induce IL-17) are induced in vitro and in vivo following infection with attenuated strains of F. tularensis (16)(17)(18). Indeed, we did find that IL-17R␣ Ϫ/Ϫ mice were more susceptible to LVS infection; however, during the course of our work, several groups reported similar findings (19)(20)(21), but no efforts were made by these groups to study the role of IL-17 during virulent F. tularensis infections.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that IL-12p35-deficient mice, as well as wildtype mice, are capable of resolving infection; however, IL-12p40-deficient mice are much more susceptible to disease, suggesting that IL-23 (a heterodimer of IL-23p19 and IL-12p40), which can induce IL-17 production, is important in resolving F. tularensis infections (39). It was also shown that intranasal LVS infection leads to increased IL-17 expression in the bronchoalveolar lavage fluid of infected mice (16), and the infection of human peripheral blood mononuclear cells (PBMCs) with LVS in vitro also induces IL-17 responses (17). In addition, the infection of human PBMCs in vitro with either Francisella novicida or type A F. tularensis SchuS4 was shown to induce IL-23p19 mRNA (18).…”
mentioning
confidence: 97%